2018
DOI: 10.1371/journal.pone.0206696
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated vizantin suppresses mucin layer penetration dependent on the flagella motility of Pseudomonas aeruginosa PAO1

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes severe infections, such as pneumonia and bacteremia. Several studies demonstrated that flagellar motility is an important virulence factor for P. aeruginosa infection. In this study, we determined whether sulfated vizantin affects P. aeruginosa flagellar motility in the absence of direct antimicrobial activity. We found that 100 μM sulfated vizantin suppressed P. aeruginosa PAO1 from penetrating through an artificial mucin layer by affecting flage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…aeruginosa, playing a role in the pathogenicity of certain mucosal infections and are essential to the virulence of the bacteria. Studies have indicated a high degree of homology between genes encoding the T3SS and those involved in flagella production . Therefore, as we observed that compound II-22 could suppress the expression of T3SS-related genes in P.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…aeruginosa, playing a role in the pathogenicity of certain mucosal infections and are essential to the virulence of the bacteria. Studies have indicated a high degree of homology between genes encoding the T3SS and those involved in flagella production . Therefore, as we observed that compound II-22 could suppress the expression of T3SS-related genes in P.…”
Section: Resultssupporting
confidence: 53%
“…Studies have indicated a high degree of homology between genes encoding the T3SS and those involved in flagella production. 25 Therefore, as we observed that compound II-22 could suppress the expression of T3SS-related genes in P. aeruginosa, we proceeded to investigate the impact of compound II-22 on the motility of P. aeruginosa. We tested the motility of P. aeruginosa with or without the addition of compound II-22.…”
Section: Effects On Other Virulence Factorsmentioning
confidence: 99%
“…Finally, after removing the ion-exchange resin, the mixture was subjected to SEC with Sephadex ® G-25 to give the desired 3. [26][27][28][29][30][31] However, the overall yield of 3 from vizantin was only 29%. Thus, we embarked on improving the synthesis method in more detail (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria were then diluted in BYE broth to OD 660 of 0.3. Transwell plates (Corning) were used for analysis of bacterial crossing of a mucin layer following a previously described protocol [80,81]. 500 μl of sterile BYE broth was added to the bottom of either empty wells, or wells containing 3.0 μm transwells.…”
Section: Mucin Coated Transwell Penetration Assaymentioning
confidence: 99%